Marine ω-3 PUFA Supplementation Enhances FFAR4 Activation and Reduces Inflammatory Markers in PBMC of Subjects with Obesity: A Randomized Controlled Trial (EPICO). - Reyes-Pérez, Samantha Desireé; Cambron-Mora, Diego; Torres-Vanegas, Joel; Mojica-Zamudio, Karla Lizette; Olaez-Ramos, Carolina Elizabeth; Lauriano-Rivera, Ramon Gerardo; Rivera-Valdés, Juan J.; Torres-Castillo, Nathaly; Valencia-Sosa, Evelyn; Rodriguez-Echevarria, Roberto; Martinez-Lopez, Erika (Nutrients, 2025)
Background: It is widely accepted that low-grade chronic inflammation in obesity worsens the metabolic state and threatens patients' lives in a long-term manner. In fact, diet therapy is the first-line treatment in which relevant nutrients such as the omega-3 polyunsaturated fatty acids (ω-3 PUFA) must be adequately consumed to counteract the established inflammation. In particular, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been identified as agonists of cellular receptors, including the free fatty acid receptor 4 (FFAR4), which regulates anti-inflammatory pathways associated with enhanced insulin sensitivity. However, the expression and activation of this receptor in peripheral blood mononuclear cells (PBMC) remains poorly investigated in humans. Objective: This study aimed to evaluate the effect of a diet supplemented with marine ω-3 PUFA on FFAR4 receptor activation and inflammatory markers in peripheral blood mononuclear cells in subjects with obesity. Methodology: A double-blind, randomized clinical trial (NCT05068557) was conducted over two months (eight weeks) in 55 obese individuals (aged 25–59 years). Participants were randomly assigned to one of two groups: an active placebo group (1.6 g/day of alpha-linolenic acid) or a marine ω-3 group (1080 mg of EPA and 720 mg of DHA). Both groups followed a dietary regimen with progressive calorie restriction (−200 kcal/day during weeks 0–4 and −400 kcal/day during weeks 4–8) in addition to supplementation. Results: Following the intervention, both groups showed significant improvements in body composition and biochemical parameters. Supplementation with EPA and DHA enhanced FFAR4 activation at the end of the intervention. Moreover, there was a reduction in the expression of JNK and IKKβ genes, as well as in serum levels of TNF-α, IL-6, and IL-18. In contrast, IL-10 levels increased significantly both within and between the groups. Conclusions: Marine ω-3 PUFA supplementation, in the context of a dietary intervention, promotes FFAR4 activation, thereby contributing to the modulation of the inflammatory response in human PBMC.